A new version of energy and elastica for curves with extended darboux frame - Vedat Asil; Talat Körpınar; Yasin Ünlütürk (Boletim da Sociedade Paranaense de Matemática, 2022)
In this work, we research geometrical interpretation involved with the energy by ED-frame field of first and second kind on orientable hypersurface in E⁴. We explore the geometric properties of some graphics by way of energy. We apply totally diverse discussion and approach to illustrate bending energy functional for ED-frame field of first and second kind. Moreover, we have an original and satisfactorily association among energy of the curve on orientable hypersurface in E⁴.